Denied odors of the aging body in the processes of significance of abuse in contemporary Chile - Guajardo Soto, Gabriel (Estado, Gobierno y Gestión Pública, 2018)
Body odor in its relation with mistreatment towards elderly has had few attention from research in the field of violence studies. This article adresses the subject starting from the results of cualitative research based on 4 discussion groups and 4 focus groups executed with the participation of self-reliant elderly between the years 2012 and 2014, Región Metropolitana, Chile. The results are the following: in middle-high and middle socioeconomic status, taboos and stigma concerning excrement and urine odors are spontanously mentioned by participants. In the mid-low and low socioeconomic status, odors concerning aged bodies do not constitute a mark. Women, old mothers and grandmothers are most likely to be the subjects of rejected odors; older men do not appear in social discourse. Finally, the article discusses the necesity to consider different dimensions and uses of the body in the delimitation of the public problem of violence towards old aged people.